Low blood pressure in psychiatric inpatients. - Masterton, G (Br Heart J, 1981)
Blood pressure recordings in 116 female psychiatric inpatients were analysed. Sixty-nine women had schizophrenia, the remainder a variety of psychiatric conditions. All had been in hospital continuously for more than one year, the average for 19 years continuously. An average of seven recordings of blood pressure per patient had been made during that time. The latest of these compared well with measurements made independently using a sphygmomanometer free from observer bias. On admission to hospital the blood pressure of these patients was close to that of two normal populations. Thereafter it failed to rise at the normal rate and after an average of 19 years, in the women having measurements made by special sphygmomanometer, systolic pressure was 28 mmHg lower than controls of the same age while diastolic pressure was 12.8 mmHg lower. Lower than control blood pressure was apparent in schizophrenic and non-schizophrenic women and in women taking no drugs, phenothiazines, and other drugs. Weight loss is an unlikely explanation: the mean weight of these women was 61.5 kg compared with 64.1 kg in a local control population of the same age. Some factor related to prolonged isolation in hospital seems more important.